Analysis of Risk Factors Associated with Pulmonary Tuberculosis Incidence in the Working Area of Caile Community Health Center, Bulukumba Regency - Andi Ruhban; Naila Dwi Mardiyanti; Ni Luh Astri Indraswari (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that attacks the lungs and bronchi. This disease is transmitted through the air. This study aimed to determine the risk factors associated with the incidence of pulmonary TB in the working area of Caile Community Health Center, Bulukumba Regency. This research used an analytical observational design with a case-control approach. The sampling technique was total sampling, with a total of 96 respondents consisting of 48 cases and 48 controls. Data were collected in March 2025. The majority of respondents were aged  50–59 years, and most were male. Data collection techniques included interviews and observations. Data were analyzed using univariate, bivariate (chi-square test), and multivariate (logistic regression) analyses.. The results showed a significant relationship between occupancy density (p = 0.001), ventilation area (p = 0.001), humidity (p = 0.002), and contact history (p = 0.001) with the incidence of pulmonary TB. Although smoking status showed no significant association in the bivariate analysis (p = 0.066), it became statistically significant in the multivariate model after controlling for confounding variables. Multivariate analysis also showed that the most dominant risk factor was contact history, with an OR value of 28.569, indicating that individuals with a history of contact with pulmonary TB patients were 28.5 times more likely to develop the disease..The study concludes that of the five variables analyzed, four were identified as risk factors for pulmonary TB incidence, with contact history being the most dominant. Efforts to prevent and control pulmonary TB should focus on improving housing conditions, enhancing ventilation quality, maintaining appropriate humidity, providing education on the dangers of smoking, and emphasizing the importance of avoiding direct contact with pulmonary TB patients, as well as strengthening contact screening by health workers.